Application of two environmental indicators for quantification of anthropization in the watershed of the stream of Ipê (Sp) - Pérez O., Diego Javier; de Carvalho, Sergio Luis (Revista de Ciencias Agrícolas, 2013)
Agriculture is one of the activities most impacting negatively on natural ecosystems and is the largest anthropogenic activity, due to land use and its strong influence on the environmental quality by pressure and occupation of space. These influences are also recorded in water bodies, thus creating a model of anthropic landscape of nature. To understand their effects needs are indicators that quantify the imbalance in ecosystems, and interactions of the components of a watershed. In this work, in this work applied the index of anthropogenic transformation, in order to identify and assess changes in soil use and occupation over the years, and the index of water quality, to test the current levels of pollution. Subsequently compares the results for the years of 2002 with the results in the years of 2011, thereby obtaining the differences between them, which showed an increase in the degradation of ecosystems in the watershed of the stream of Ipê and consequences of these changes by increasing levels of pollution produced water resources of the basin.